Specialty Coffee Cupping Score Prediction with General Regression Neural Network (GRNN) - Christian, Yuriko; Darmawan, I Dewa Made Bayu Atmaja (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Coffee is a plant that can be processed into beverages. The cupping score is a score for a coffee quality graded with an expert called Q grader. The cupping score will decide if a coffee may be called as specialty coffee. In this research, the cupping score will be predicted by the coffee properties and did not involve the Q grader for giving the score. The prediction of the score is obtained by using the GRNN method. The experiment consists of finding when the MAE and the MSE are converged and find the neuron's best number. The model's performance is measured with MSE and MAE with the best MSE value of 0.097 and MAE value 0.245.